"ECO TEAM" PROJECT AND ITS APPLICATION TO EDUCATION (Academicia Globe: Inderscience Research, 2023)
In this article, the implementation of the "ECO team" project, which is part of classroom and extracurricular activities, its peculiarities, its role and importance in the formation of eco-aesthetic competence, the conditions and stages of its introduction in school education, the role of school officials and pedagogues, this The importance of making a plan of work with parents is explained in detail. The similarities and peculiarities of the "ECO team" project with the work carried out for the formation of eco-aesthetic culture among students in foreign schools are described.